The Framework of the Civil Servants’ Education in the Conditions of Sustainable Development of the Republic of Belarus - Sidorchuk, Irina; Akhrymenka, Aleksei; Basko, Volha; Grigoriev, Alexei; Parfenchyk, Anton (European Journal of Sustainable Development, 2019)
Achieving the goals of sustainable development largely depends on the state machinery effectiveness and the professionalism of civil servants. Continuous education (life-long training) is an effective tool for ensuring competence level of civil servants. According to the results of the analysis of the education system of civil servants, it can be argued that in the Republic of Belarus it has developed a mixed framework of education for civil servants, which is characterized by a combination of innovative and traditional forms and teaching methods aimed at their professional and personal development. The training of civil servants is carried out within the annual governmental order. The existing educational framework was developed before the adoption of the 2030 Agenda, in this regard, the education of public servants does not fully take into account the paradigm of sustainable development. The solution is seen in the transition from the annual government order for training of civil servants to long-term, medium-term and short-term planning of their training, which correlates with the Sustainable Development Goals. It is also important to implement the principle of inclusion in education. This will entail not only the improvement of the scientific and methodological support of the educational process and the creation of new educational programs, but also an increase in the requirements for the level of teachers training and the intensification of the students role. We also believe that the use of advanced foreign experience in the learning process will strengthen the personnel capacity of the state machinery and promptly implement changes to reflect the new realities. The listed aspects of the civil servants education framework transformation in the Republic of Belarus can become potential growth points that in the long term will allow Belarus to achieve the Sustainable Development Goals.